CHANGES IN THE UTERUS AND VAGINA OF RATS WITH EXPERIMENTALLY INDUCED DIABETES AND THE EFFECT OF LYCOPENE ON THE CHANGES - Mustafa Yildiz; Mustafa Sandikci (Slovenian Veterinary Research, 2016)
Summary:The aims of this study were to identify the changes that occurred in the uterus and vagina of rats with experimental diabetes, and the effects of orally administered lycopene on these changes. For this research, 30 four-month-old female Wistar Albino rats were used. Experimental diabetes was induced using a single dose of 50 mg/kg streptozotocin (STZ). The control and diabetic rats were randomly separated into 4 groups as follows: control+corn oil, control+lycopene, diabetes+corn oil and diabetes+lycopene.Crossman's triple staining and the Periodic Acid Schiff (PAS) methods were applied for the uterine and vaginal slides. Additionally, the uterus was stained with Alcian Blue (AB) pH: 2.5. While the number of glands, thickness of the endometrium, and PAS positive reaction in the glandular epithelium decreased, the AB positive reaction in the glandular epithelium increased in the uterus with the effects of diabetes. In the vagina, it was observed that the height of the lamina epithelialis and the thickness of the tunica muscularis decreased in the diabetes+corn oil group, compared with the control+corn oil. Also, the thickness of the tunica muscularis increased in the diabetes+lycopene group, compared with the diabetes+corn oil group. The changes caused by diabetes in the uterus and vagina, as well as the existence of the protective qualities of lycopene were revealed for the first time, to the best of our knowledge. Key words: experimental diabetes; lycopene; rat; uterus; vagina